Climate extreme events and climate change are forced by extortionate free-riders - an economic experiment (dataset) - Innocenti, S; Milinski, M (University of Oxford, 2024)
This document (xlsx) contains data emerging from an economic experiment conducted in January-February 2023 by Manfred Milinski and Stefania Innocenti.